How ICT Interfaces with Structural Issues in Indian Agriculture - Abhishek Beriya; V.N. Saroja (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
Governments across the globe and more so in the developing country context, have a primary responsibility of ensuring food security for their population and India is no exception. The Indian government is also responsible for the well-being of its farmers because approx half the population depends on agriculture for their livelihood. Given this background, our colonial experience and the environment of deficit and food insecurity in the decades even after our independence in 1947, Indian agriculture is inextricably tied to the state and its institutions particularly the governments both at the state and federal levels. The government is the sole entity responsible for maintenance of land records, and the primary entity responsible for comprehensive collection and collation of agricultural data and ensuring marketing of agricultural produce. Thus it is also the repository and custodian of all such data. Governments in India, through mechanisms like the essential commodities act and the control over export and import decisions exercise a dominant say in pricing and inflation of agricultural goods. It is the primary agency for weather forecasts and provides relief in times of natural disasters which adversely affect agriculture. Agriculture credit is also facilitated by government policies. The federal government and the state governments carry out all these activities through their various ministries/departments/agencies and policies for the agricultural sector. (...)
Keywords: 330